Emotional experiences and gender roles of men with fibromyalgia syndrome: a cross-cultural qualitative study - Montesó-Curto, Pilar; Toussaint, Loren; Kueny, Angela; Ruschak, Ilga; Lunn, Shannon; Rosselló, Lluís; Campoy, Carme; Clark, Stephanie; Luedtke, Connie; Gonçalves, Alessandra Queiroga; Aguilar Martín, Carina; Vincent, Ann; et al. (Frontiers in Medicine, 2024)
Introduction: Gender roles may impact men with fibromyalgia, causing a high number of negative emotional states and affective disorders. There are few studies that detect men's high emotional suffering. This study examined the emotional experience of men with fibromyalgia. Methods: A qualitative cross-cultural study utilized inductive thematic analysis was performed at the Fibromyalgia and Chronic Fatigue Unit Santa Maria University Hospital in Spain, the Fibromyalgia and Chronic Fatigue Clinic at Mayo Clinic in the US, and volunteers from the Winneshiek County in the US A total of 17 participants, 10 men from Spain and 7 men from the US were included. Results: Three themes related to feelings/emotions emerged: 1) psychological level; 2) social level; 3) physical level. Men with fibromyalgia from Spain and the US experienced many negative emotions. Men often experience negative emotions that are worsened by common misunderstandings and social biases/stigma about their condition. Conclusion/Implications: A proper assessment of emotions when evaluating the global health of men with fibromyalgia as well as the provision of emotional support would improve their mental health and therefore their overall physical health. Emotional management should be incorporated into all treatment protocols for fibromyalgia, especially for men given the gender stigma. Health policies designed by legislators, policymakers, and support agencies must be accompanied by education in gender role concepts to improve the emotions of men with FMS. The mass media will be essential for the disclosure of the emotional suffering of male patients so that society might better understand them.